Chronopharmacology of alcoholism - E. V. Filippova; Yu. K. Kondrashova; Yu. Sh. Tagoev (Лечащий Врач)
The article presents an analysis of information from literary sources devoted to the study of the chronopharmacology of alcoholism. For the treatment of alcoholism, an integrated approach is used, which is determined by the severity of the patient's condition and the individual characteristics of the symptoms. Due to the ability of pharmacological compounds to interfere during rhythmic processes at all levels of the organization of the biosystem, the chronopharmacological effect of drugs may be useful or undesirable. Chronic alcohol intoxication is characterized by a high degree of complications from the cardiovascular, nervous systems, liver and gastrointestinal tract. A reliable means of pathogenetic pharmacotherapy of alcoholism has not yet been developed. At the same time, medications are used mainly for the relief of withdrawal symptoms. One of the first places in the treatment of alcohol withdrawal syndrome, accompanied by anxiety, fear and anxiety, is occupied by depressants. However, the expansion of their use in the Russian Federation for the treatment of alcoholism remains unfounded. Since alcoholism causes extremely diverse mental disorders in their clinical manifestations and severity, a wide range of psychotropic drugs is used for their treatment. For antihypoxic and detoxifying therapy, energy-correcting agents are also used. Alcohol withdrawal syndrome with a predominance of neurosis-like and vegetative-vascular disorders is an indication for the use of drugs from the class of antioxidants. They combine the properties of tranquilizers and nootropics, without having a toxic effect on the heart and protecting the myocardium in hypoxia. However, at the moment there is a lack of information about the effectiveness of their use in alcohol withdrawal.